The Power of Perception: Unpacking the Role of Negative Thinking in High School Students’ Test Anxiety - Damla Kahraman; Elif Özüm Kuş Işık; Mehmet Hakan Türkçapar; Cemile Dur Öztürk; Duygu Betül Özkanca; Nilüfer Koçtürk; Eyüp Sabır Erbiçer; Türkan Doğan; Ercan Akın (e-Kafkas Eğitim Araştırmaları Dergisi)
The main purpose of this study is to determine the factors that contribute to the formation and maintenance of negative cognitions in adolescents. The present study employs a qualitative methodology to examine test-related negative cognitions of senior high school students with test anxiety. The consensus qualitative research (CQR) method was employed in the study design. Subsequently, fifteen randomly selected students were administered an inventory prepared using semi-structured interview questions, test anxiety, cognitive and behavioral therapy literature, and expert opinions. It was revealed that students' negative cognitions were clustered in four domains: self-oriented, other-oriented, future-oriented, and test-oriented. The self-orientated domain had three themes: self-criticism, lack of confidence, and high self-expectations. Other-oriented domain contained two themes: blaming others and concern about the social consequences of failing. The future-orientated domain had two themes: reading the future and intolerance to uncertainty. Lastly, the test-oriented domain had three themes: distraction during test, inefficient test-taking strategies, and negative study skills assessment. The study’s findings revealed that students have negative cognitions that have emerged as thoughts related to self, others, the future, and testing itself. These negative thoughts may affect students’ test anxiety levels, confidence, academic performance, and well-being. These findings were generally consistent with the literature and were discussed considering the relevant literature. It is suggested that mental health professionals and educators can use the cognitions addressed within the scope of the research to support students to improve their well-being, academic performance and resilience.